Fatigue presentation, severity, and related outcomes in a prospective cohort following post-COVID-19 hospitalization in British Columbia, Canada - Magel, Tianna; Meagher, Emily; Boulter, Travis; Albert, Arianne; Tsai, Melody; Muñoz, Carola; Carlsten, Chris; Johnston, James; Wong, Alyson W.; Shah, Aditi; Ryerson, Chris; Mckay, Rhonda Jane; et al. (Frontiers in Medicine, 2023)
Introduction: Increasing evidence on long-term health outcomes following SARS CoV-2 infection shows post-viral symptoms can persist for months. These symptoms are often consistent with those of Myalgic Encephalomyelitis or Chronic Fatigue Syndrome (ME/CFS). The aim of the present study was to examine the prevalence and outcome predictors of post-viral fatigue and related symptoms 3- and 6-months following symptom onset. Methods: A prospective cohort of patients hospitalized with Coronavirus disease (COVID-19) (n=88) were recruited from a Post-COVID-19 Respiratory Clinic (PCRC) in Vancouver, Canada to examine predictors of long-term fatigue and substantial fatigue. Multivariable mixed effects analyses examined the relationship between patient predictors, including pre-existing comorbidities, patient reported outcome measures, and fatigue and substantial fatigue at follow-up. Results: Patients exhibiting fatigue or substantial fatigue were 58 (67%) and 14 (16%) at 3 months and 47 (60%) and 6 (7%) at 6 months post-infection, respectively. Adjusted analysis, for sex, age, and time, revealed the number of pre-existing comorbidities to be associated with fatigue (OR 2.21; 95% CI 1.09-4.49; 0.028) and substantial fatigue (OR 1.73; 95% CI 1.06-2.95; 0.033) at 3 months follow-up. Except for shortness of breath, self-care, and follow-up time, all follow-up variables were found to be associated with fatigue and substantial fatigue at 3 months. Conclusion: Fatigue and substantial fatigue are common after COVID-19 infection, and decrease from 3 to 6 months. However, a significant number of patients continue to exhibit long-term fatigue at 6 months follow-up. Further research is needed to clarify the causality of viral infections in the development and severity of fatigue as a symptom and in meeting post-viral fatigue syndrome or ME/CFS diagnostic criteria.